Determination of Adsorption Isotherm model best fit for methanol leaf extract of Securinega virosa as corrosion inhibitor for corrosion of mild steel in HCl - Adejo, S. O.; Ekwenchi, M. M.; Gbertyo, J. A.; Menengea, T.; Ogbodo, J. O. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The adsorption isotherm model best fit of the methanol leaf extract of Securinega virosa as corrosion inhibitor for the corrosion of mild steel in 2 M HCl medium was determined with the assistance of the Adejo-Ekwenchi adsorption isotherm. The corrosion inhibition study was carried out using the weight loss method at the temperature range of 301 K to 313 K.Â  The inhibition efficiency, %IE, of the extract was found to increase with increase in both concentration and temperature. On the account of, R2 this adsorption process well fitted into Langmuir, Freundlich, Temkin isotherm, Flory-Huggins and Adejo-Ekwenchi models. However, through the parameter b of the Adejo-Ekwenchi isotherm, which clearly shows the adsorption process to be chemisorption, the best isotherm fit for the extract has been resolved to be the Langmuir isotherm and Temkin isotherm models.Â 